Public Housing Relocation of Older Adults in Atlanta: Challenging the Aging in Place Concept - Laquanda R. Jackson (Journal of Public and Professional Sociology, 2015)
In 2007 AHA demolished two senior high-rise buildings causing the forcible removal of older African American residents who may have wanted to age in place due to community attachment. Aging in place and community attachment are concepts that describe the strong social-psychological attraction to a specific location among older long-term residents (McAuley 1998). This thesis examines if community attachment differ for residents who were forced to relocate and those who were able to age in place. Using longitudinal data from the GSU Urban Health Initiative, I looked at relocated and non-relocating senior public housing residents’ community attachment as it relates to tenure and distance to needed services pre and post-move to explore if community attachment was influenced. Findings reveal that community attachment and aging in place are more complex than originally realized. Tenure and distances to needed services is only one aspect of unique aging for senior minority residents.